EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH: STUDI LAPANGAN TENTANG PRAKTIK DAN TANTANGAN EVALUASI - Firma Deli; Julhadi Julhadi (Ensiklopedia of Journal, 2026)
This study aims to evaluate the implementation of assessment in Islamic Religious Education (PAI) learning at madrasah, focusing on planning, implementation, and the utilization of assessment results. Assessment in PAI learning has distinctive characteristics because it encompasses the evaluation of students’ cognitive, affective, and psychomotor domains. This study employed a qualitative approach with a field research design. The research subjects consisted of Islamic Religious Education teachers, the head of the madrasah, and students. Data were collected through classroom observations, in-depth interviews, and document analysis. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings reveal that PAI learning assessment has been planned and implemented continuously; however, it is still predominantly focused on cognitive assessment. The assessment of affective and psychomotor aspects has not been carried out systematically due to limited instruments and teachers’ understanding. Moreover, the use of assessment results as a basis for improving instructional practices has not been optimal. This study recommends strengthening teachers’ competencies in authentic assessment and developing comprehensive assessment instruments to enhance the quality of PAI learning.Keywords: learning assessment; Islamic religious education; field research; madrasah